2010
DOI: 10.1002/bjs.6803
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of laparoscopic versus open donor nephrectomy

Abstract: LDN removes some of the disincentives to live donation without compromising the outcome of the recipient transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 20 publications
5
74
0
4
Order By: Relevance
“…Therefore, graft survival is 5% more in LDN compared with ODN. Although, this is not clinically significant, long-term follow-up of 2 other RCTs carried out by Nicholson and associates 13 and Dolsand associates 14 were 5% superior in LDN when compared with ODN. Greco and associates published a systematic review after analysis of more than 50 comparative studies about the different techniques of donor nephrectomy (open, laparoscopy, hand-assisted laparoscopy) according to perioperative parameters and graft outcome, and concluded that even though WITs are longer in the laparoscopic group, postoperative graft function was not significantly different between these 3 modalities.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, graft survival is 5% more in LDN compared with ODN. Although, this is not clinically significant, long-term follow-up of 2 other RCTs carried out by Nicholson and associates 13 and Dolsand associates 14 were 5% superior in LDN when compared with ODN. Greco and associates published a systematic review after analysis of more than 50 comparative studies about the different techniques of donor nephrectomy (open, laparoscopy, hand-assisted laparoscopy) according to perioperative parameters and graft outcome, and concluded that even though WITs are longer in the laparoscopic group, postoperative graft function was not significantly different between these 3 modalities.…”
Section: Discussionmentioning
confidence: 66%
“…Other approaches such as advances in surgical techniques can encourage and improve living donation concept. The development of laparoscopic nephrectomy was a tremendous advance because it decreased disfigurement and reduced pain and time to recovery [78].…”
Section: Policies To Enhance Living Donationmentioning
confidence: 99%
“…14 While in recent literature the intraoperative complication rate has been found to be greater in patients undergoing more conventional open approaches, 15 a number of earlier reports have suggested the opposite to be true. Other studies have also reported no appreciable differences in complications between either approach.…”
Section: Mini-open Vs Laparoscopic Nephrectomy For Kidney Transplantmentioning
confidence: 99%
“…22 Laparoscopic donors also benefit from a reduced hospital LOS that has been well-documented in the literature. [14][15][16][18][19][20][23][24][25] Despite the shorter hospital stay, the higher cost of surgical equipment needed for laparoscopy leads to a higher overall cost when compared to mini-ODN ($5132 vs. rampersad et al…”
Section: Mini-open Vs Laparoscopic Nephrectomy For Kidney Transplantmentioning
confidence: 99%